Impact of Dietary Protein on Growth, Feed utilization and Body composition of Puntius parrah - R., Bindhu; N., Ramanujan; C., Sambhu (Fishery Technology, 2025)
The juveniles of Puntius parrah were fed with fishmeal based protein diets at concentrations of 10%, 20%, 30%, 40% and 50% by weight for a period of 120 days in cement cisterns. Protein diet at 50% produced superior growth, maximum food consumption, high conversiorf efficiency and better protein digestibility. Digestive enzyme activity and RNA/ DNA ratio were higher in 50% protein diet fed fish. The total dry matter and protein content of the body showed high values in the fish fed with 50% protein diet. 50% protein diet is found optimum for growth enhancement in Puntius parrah.